A pilot study on the acoustic effects of a pseudo-palatal plate on speech: Implications for articulatory rehabilitation devices - Seong Tak Woo; Sungdae Na (PLoS ONE, 2026)
Intraoral palatal plates used in electropalatography (EPG) and tongue-interface systems are designed to monitor articulatory movement with minimal disruption to speech. However, their presence may subtly influence acoustic characteristics by altering tongue mobility and intraoral airflow. This study examines the acoustic effects of a pseudo-palatal plate during the articulation of consonants and vowels. Speech samples from healthy adults were recorded with and without the plate and analyzed using spectral and phonatory measures, including Mel-frequency cepstral coefficients (MFCCs), second formant (F2) slope, jitter, shimmer, harmonics-to-noise ratio (HNR), and quadrilateral vowel space area (qVSA). MFCC-based correlation coefficients and F2 slopes remained highly consistent across conditions, indicating minimal impact on consonant articulation. Shimmer (−0.72%), HNR (+2.5 dB), and qVSA (−24.1%) exhibited directionally consistent changes, with qVSA trending toward reduction; however, overall variation was limited. Vowel formant structures and consonant production were preserved mainly, suggesting that the palatal plate did not significantly impair vocal function. These findings support the interpretation that observed acoustic shifts are more consistent with filter-level effects than with changes at the glottal source. Although palatal plates may introduce minor acoustic variations, their impact on speech production appears minimal, reinforcing their suitability for therapeutic and assistive use, provided that acoustic considerations are addressed during design and clinical implementation.